Impact of vitamin D level and supplementation on systemic lupus erythematosus patients during COVID-19 pandemic - Yasmin Adel,; Mohamed Elgamal,; Sherehan Adel Abdelsalam, (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to assess the impact of serum vitamin D level in systemic lupus erythematosus (SLE) patients with novel coronavirus-2019 (COVID-19) disease on severity of infection, duration of COVID-19 disease course, and fatigue development as a complication of both SLE and COVID-19. Patients and methods: Between April 2020 and January 2021, a total of 38 patients (31 males, 7 females; mean age: 49.2±8.1 years; range, 38 to 65 years) who were previously diagnosed with SLE and on different lines of lupus management were included. The patients presented to chest outpatient clinic and emergency hospital with manifestations suggesting COVID-19 infection. Vitamin D levels were measured in serum by enzymelinked immunosorbent assay (ELISA). Vitamin D supplement was added to treatment protocols for COVID-19. Results: Thirteen (34.2%) patients had normal baseline serum vitamin D levels (≥30 ng/mL), nine (23.7%) patients had vitamin D insufficiency (21 to 29 ng/mL), and 16 (42.1%) patients had vitamin D deficiency (≤20 ng/mL). Low vitamin D levels (insufficiency & deficiency) patients had long SLE disease duration (p=0.06). Also, there was a significant long time spent until recovery from COVID-19 infection in low vitamin D levels (insufficiency & deficiency) patient groups versus those with normal vitamin D (p=0.019). Low baseline vitamin D level patients mainly presented with severe COVID19 symptoms (p=0.04). Patients recovered from COVID-19 had normal vitamin D levels than those who died or were lost to follow-up (p=0.07). After recovery from COVID-19, fatigue was more common in SLE patients with low baseline vitamin D level. Conclusion: Vitamin D seems to play a certain role in the management of COVID-19 infection in SLE patients. Patients with normal vitamin D levels have less severe symptoms, shorter time to recovery, improved COVID-19 outcomes, and less development of fatigue after COVID-19 infection.